Effect of project-based learning and communication skills on students’ problem solving and reasoning - Ariyani Muljo; I Nyoman Sudana Degeng; Cholis Sa’dijah (Universitas Muhammadiyah Malang, 2025)
This study aims to determine the effect of project-based learning model and communication skills on problem solving and reasoning skills of 8th grade students of Nurul Huda Islamic Junior High School. The study used an experimental design with two groups, namely the experimental group that applied the project-based learning model and the control group that used the conventional learning model. The research population was students of Nurul Huda Islamic Junior High School Malang City. Data analysis used two-way MANOVA. The results showed: 1) There is a significant difference in problem solving ability between students who learn with project-based and conventional learning models; 2) There is a significant difference in reasoning ability between students who learn with project-based and conventional learning models; 3) There is no difference in problem solving ability between students with high and low communication skills; 4) There is no difference in reasoning ability between students with high and low communication skills; 5) There is no interaction between learning models and communication skills on problem solving ability; 6) There is an interaction between learning models and communication skills on students' reasoning ability. The project-based learning model is proven to be more effective in improving students' problem solving and mathematical reasoning skills than the conventional model.